Design and optimization of a spiral separator for enhanced chromite recovery and sustainability - Navid Hosseini Alaee; Jafar Sargheyni; Mehdi Pezeshkan; Pooria Kianoush (Cleaner Engineering and Technology)
The increasing demand for chromite, coupled with rising mining and processing costs, necessitates the development of more efficient mineral processing technologies. This research presents a novel spiral separator specifically designed to produce chromite concentrate from low-grade ores, addressing both resource efficiency and environmental sustainability. The efficiency and performance of this separator depend on its technical and operational characteristics. Utilizing advanced mathematical modeling techniques, including Reynolds-averaged turbulent Navier-Stokes equations and the Bagnold effect, the study simulates slurry behavior on the spiral separator's surface and the segregation of light and heavy materials. The innovative design of the spiral separator incorporates unique geometric features that enhance particle stratification, leading to significant improvements in operational performance. The resulting prototype demonstrates significant enhancements in operational performance, achieving improved recovery rates and reduced energy consumption compared to traditional methods. Additionally, the separator's design minimizes waste generation, contributing to a more sustainable processing approach. These findings underscore the spiral separator's potential to improve economic viability in chromite processing while mitigating environmental impacts, making it a promising alternative to existing technologies. This research contributes to the field of mineral processing by providing a tailored solution for low-grade chromite recovery and highlights the importance of integrating innovative engineering practices to promote sustainability in resource extraction.